(untitled) (Global Journal of Management and Business Research, 2017)
The article deals with the theoretical aspects of the distribution the formation sources of property assets component of farm property, including real possibilities, time limits, forms and methods of financial resources. The variability of factors that covers all possible risks of financing the economic activity was determined. A systematic approach to the evaluation of the dynamic trend that slows financing risk, taking into account indicators of sustainable financial condition of agricultural enterprises was proposed.